Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4733
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Diesel Spray Impingement on a Flat Plate: Effects of Injection Conditions

Abstract: Advanced injection strategies for internal combustion engines have been extensively studied although there still exists a significant fundamental knowledge gap on the mechanism for high-pressure spray interaction with the piston surface and chamber wall in the internal combustion engine. The current study focuses on providing qualitative and quantitative information on spray-wall impingement and its characteristics by expanding the range of operating parameters under engine-like conditions. Parameters consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Detailed information of the combustion vessel can be found in a previous study. 33 A single-hole, off-axis, Bosch LBZ diesel injector was adopted. The nozzle size is 200 µm in diameter.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information of the combustion vessel can be found in a previous study. 33 A single-hole, off-axis, Bosch LBZ diesel injector was adopted. The nozzle size is 200 µm in diameter.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…axial/radial expansion distances at axial direction) were obtained by tracking the boundary of the spray expansion pattern in our previous study. 33 The procedure of boundary tracking method in this study is shown in Figure 5.…”
Section: Image Post-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle of impact is also an important factor in spray characteristics [10], [11], [22]. Studies have shown that lower impact angles tend to result in faster spray penetration [10]- [12], [22], [23]. An optimal impact angle can provide better fuel distribution and higher combustion efficiency [4], [9].…”
Section: Introductionmentioning
confidence: 99%
“…After spray hitting the wall, the spray radius and height is changed, which will affect the mixing of fuel and air, and further affect the engine performance and exhaust particulate emissions. Therefore, it is significant to study the phenomenon of spray impingement on diesel engine [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%